Pengujian Black Box pada Sistem Informasi Penjualan Buku Berbasis Web dengan Teknik Equivalent Partitions - Shaleh, Ibnu Adha; Prayogi, Juma; Pirdaus, Perdi; Syawal, Riky; Saifudin, Aries (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
With the development of information technology, then we should also follow these developments so that we will not miss any information. At this time there are many businesses who market their products and sell them by utilizing information technology as well as by using an information system based on the website. In the utilization of the information system, the quality of the software built or made becomes very important, because by having good software it will also have an impact with the convenience of the user. The higher the quality of the software created, the more convenient the user will use it. And to be able to see how qualified the software is made then we can do a software test. In software testing there are methods that can be used such as Whitebox Testing and Blackbox Testing that have been widely applied. In this study, the method that will be used is Blackbox Testing which will be implemented in the website-based book sales information system, with the aim that we can find out if the functions in the program will be in accordance with what is expected. In Blackbox testing method there are many techniques that can be used, one of which is Equvalent Partitions technique which is a testing technique based on input on the existing form, and here formya refers to the website-based book sales information system. This test will see if the function or form that is the test material will result in a valid or invalid value. If the result is valid then the software is in accordance with what we want and if it is not valid then there is an error and can be fixed, so that later the software to be used has good quality.